1970
DOI: 10.1029/ja075i010p01854
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency noise observed in the distant magnetosphere with OGO 1

Abstract: Two new types of low‐frequency noise, designated ‘broadband’ and ‘highpass’ have been detected in the distant magnetosphere by the VLF/LF experiment on the OGO 1 satellite. Broadband noise extends over the entire range of observations from 0.2 to 100 kHz and the intensity decreases with increasing frequency. It occurs in bursts having durations of a few minutes or less. It shows no connection with any of the expected plasma cutoff or resonance frequencies and is believed to be a nonpropagating disturbance gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 14 publications
(9 reference statements)
0
46
0
1
Order By: Relevance
“…The first observations of this radiation were by Benediktov et al (1968) who detected a radio emission of unknown origin escaping from the Earth at frequencies of 725 and 1100 kHz that was correlated with the Kp planetary magnetic disturbance index. Dunckel et al (1970) also observed what they termed high-pass noise, primarily due to the low frequency part of the spectrum below about 100 kHz. A few years later, Gurnett (1974) showed that the radiation had its peak intensity in the frequency range from about 100 to 500 kHz, that it was very intense, approximately 10 9 Watts of total radiated power, and that it was closely correlated with the occurrence of discrete auroral arcs.…”
Section: Auroral Kilometric Radiationmentioning
confidence: 99%
“…The first observations of this radiation were by Benediktov et al (1968) who detected a radio emission of unknown origin escaping from the Earth at frequencies of 725 and 1100 kHz that was correlated with the Kp planetary magnetic disturbance index. Dunckel et al (1970) also observed what they termed high-pass noise, primarily due to the low frequency part of the spectrum below about 100 kHz. A few years later, Gurnett (1974) showed that the radiation had its peak intensity in the frequency range from about 100 to 500 kHz, that it was very intense, approximately 10 9 Watts of total radiated power, and that it was closely correlated with the occurrence of discrete auroral arcs.…”
Section: Auroral Kilometric Radiationmentioning
confidence: 99%
“…Although many spacecraft have made observations of these rad io emissions , including OGO 1 [ Dunckel et al, 1970] , IMP 6 [Brown, 1973;Gurnett , 1971d , Hawkeye 1 [ Kurth et al , 1 975 ] , IMP 8 [Gurnett, 1975] , and RAE 2 [Alexander and Kaiser, 1976] , up to the present time none have ;L taiued measurements at low-altitudes over the auroral zones wherẽ~~ ~~r ora l kilome tric radia tion is bel ieved to be ge nerated . Fortu-:~ately, because of changes in the orbit parameters after launch, the polar-orbiting Hawkeye 1 spacecraft , which was launched on June 3, 19714, has recently been able to prov~.de some limi ted coverage of this very interesting region.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors (Renediktov et al, 1968;Dunckel et al, 1970;Gurnett, 1974;Kaiser and Alexander, 1977) have shown that the intense magnetospheric radio emissions known as terrestrial kilometric radiation (TKR) or auroral kilometric radiation (AKR) are correlated both in occurrence and in intensity with magnetospheric substorms as indicated by the auroral electrojet index (AE). In the most detailed study to date, Voots et al (1977) showed that TKR can be a very reliable indicator of auroral disturbances since TKR power flux density and AE are well correlated on a coarse time scale (z 1 hr).…”
mentioning
confidence: 99%